Antenatal Risk Factors for the Birth of Little Birth Babies With Pre-Eclampsia (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2023)
The review identified the greatest risk factors for preterm birth in preeclampsia and examined adverse neonatal outcomes. A conjugation table was compiled based on the identified risk factors and the odds ratio (OR) was determined.